Cassava varietal improvement in Asia - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
In April 1983 a branch of CIAT's Cassava Program was established in Bangkok, Thailand, to help Asian national cassava programs utilize CIAT technology more directly; CIAT's main involvement is in germplasm utilization and development, training, and communications. Sexual seeds have been the major means of germplasm transfer, and during the last 10 yr more than 100,000 hybrid seeds from approx. 1800 crosses have been distributed to cassava breeding programs in Thailand, Indonesia, Philippines, China, Malaysia, India, Vietnam, and Republic of China (Taiwan). In Thailand CIAT germplasm has been effectively evaluated and used, and in Malaysia proper evaluation has been made. In the Philippines, cassava production has increased. Due to limited resources Indonesia is struggling to achieve a scheme of germplasm evaluation and utilization that satisfies national needs. India is not interested in CIAT germplasm due to its lack of mosaic resistance. Finally, in China lowland materials are being tested in subtropical climates. Tables and figures of results of yield trials of different clones and countries are included. (CIAT)